2016
DOI: 10.4049/jimmunol.1402193
|View full text |Cite
|
Sign up to set email alerts
|

CD275-Independent IL-17–Producing T Follicular Helper–like Cells in Lymphopenic Autoimmune-Prone Mice

Abstract: T cells undergo homeostatic expansion and acquire an activated phenotype in lymphopenic microenvironments. Restoration of normal lymphocyte numbers typically re-establishes normal homeostasis, and proinflammatory cytokine production returns to baseline. Mice deficient in guanine nucleotide exchange factor RasGRP1 exhibit dysregulated homeostatic expansion, which manifests as lymphoproliferative disease with autoantibody production. Our previous work revealed that autoreactive B cells lacking RasGRP1 break tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…CD278-CD275 interactions are considered key for the generation of T follicular helper cells (Tfh) 53, 54 . In recent work, we demonstrated that Rasgrp1 -deficient mice have increased frequency and number of IL-17A-producing Tfh cells 55 . Interestingly, Rasgrp1 -deficient mice also lacking CD275 still produced Tfh17 cells, formed germinal centers, and produced similar titers of anti-nuclear autoantibodies compared with mice lacking only RasGRP1.…”
Section: Discussionmentioning
confidence: 95%
“…CD278-CD275 interactions are considered key for the generation of T follicular helper cells (Tfh) 53, 54 . In recent work, we demonstrated that Rasgrp1 -deficient mice have increased frequency and number of IL-17A-producing Tfh cells 55 . Interestingly, Rasgrp1 -deficient mice also lacking CD275 still produced Tfh17 cells, formed germinal centers, and produced similar titers of anti-nuclear autoantibodies compared with mice lacking only RasGRP1.…”
Section: Discussionmentioning
confidence: 95%
“…ICOS is well known to be needed for the differentiation and function of Tfh cells (20), but the requirement of ICOS for Tfh cells can be overcome by the presence of abundant autoantigens and a large number of activated antigen-specific B cells (20,40), reflecting realistic in vivo conditions in human SLE and leading to nonselective DNA recognition by IgG anti-dsDNA from lupus patients (41). Likewise, while immunizations of conventional mice and lupus-prone NZB/NZW mice with pathogen DNA result in the generation of IgG anti-dsDNA, such antibodies from conventional mice are specific for immunizing pathogen DNA, whereas antibodies from NZB/NZW mice have cross-reactivity (42).…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests Dapk2 as an inhibitory regulator of T-cell help for GC formation. Cytokines produced by Th1, Th2, and Th17 cells have all been implicated in GC responses ( Nakayamada et al, 2011 ; Reinhardt et al, 2009 ; Smith et al, 2016 ), although Dapk2 KO T cells show no appreciable defect in generating those cytokine-producing subsets in vitro . The inhibitory effect of Dapk2 on GC formation is likely due to its suppression of antigen-specific T-B adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Following this early phase of cognate T-B interactions, T cells migrate into the follicle in conjunction with activated B cells and become follicular helper T (Tfh) cells that highly express chemokine receptor CXCR5, co-signaling molecule ICOS and PD-1, and the transcription factor Bcl6 ( Crotty, 2011 ; Pratama and Vinuesa, 2014 ; Wan et al, 2019 ). While the precise relationship between so-defined Tfh cells and other helper subsets defined by cytokine profiles is still debated, it has become clear that Tfh cells can produce a variety of effector cytokines including IL-4, IL-9, IL-10, IL-13, IL-17, IL-21, and IFN-γ ( Chtanova et al, 2004 ; Gowthaman et al, 2019 ; Linterman et al, 2011 ; Nakayamada et al, 2011 ; Reinhardt et al, 2009 ; Smith et al, 2016 ; Wang et al, 2017 ). Each of these cytokines has been shown to play a specific role in regulating certain aspects of the GC response.…”
Section: Introductionmentioning
confidence: 99%